Effectiveness of an Education Program on Youth's Awareness towards Household Waste Control - Sarkees, alaa; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2013)
Objective: determine the effectiveness of an education program on youth's level of awareness towardshousehold waste control.Methodology: A Quazi-experimental study was conducted. Non-probability (quota sample) of (80) youngpersons is selected from Baghdad Governorate. They are divided into two equal groups of (40) subjects for thestudy group which is exposed to the household waste control educational program. The remaining is thecontrol group which is not exposed to the educational program.Results: The findings of the study indicated that youth of the study group have got benefits from theimplementation of the educational program towards household waste control and change has occurred totheir awareness towards such control.Recommendations: The study recommends that the role of television upon youth's awareness can beactivated through presenting the household waste control educational program which may facilitate to bringthe information for long distance area and increase wide-range awareness of youth.